2020
DOI: 10.1186/s12872-020-01391-7
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of JAK2/STAT3/SOCS3 signaling attenuates atherosclerosis in rabbit

Abstract: Background: Previous studies have indicated that the JAK/STAT signaling pathway is involved in modulating arterial adventitia inflammation response. In this study, we designed experiments to further investigate the effect of JAK2/STAT3/SOCS3 signaling in rabbit atherosclerosis process.Methods: Atherosclerosis was induced in the abdominal arteries of rabbits by balloon injury of the aorta supplemented by the atherogenic diet. Simultaneously, in the process of atherosclerosis, animals underwent either ruxolitini… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(41 citation statements)
references
References 37 publications
2
39
0
Order By: Relevance
“…Due to their powerful anti-inflammatory effects, it is plausible that DMARDs may also prevent cardiovascular events. Inhibition of cytokines, such as tumor necrosis factor (TNF) and interleukins (ILs), and janus kinase (JAK) have been reported to limit inflammatory mechanisms implicated in athero-thrombosis through studies in animal models 10 12 . Most commonly prescribed biologic and targeted synthetic DMARDs such as TNF-alpha (α) inhibitors, IL-1 beta (β) & IL-12/23 inhibitors and JAK-1/2 inhibitors have been tested in randomized controlled trials within a variety of different populations that are at risk of MACE, such as people with rheumatoid arthritis and psoriasis 13 17 .…”
Section: Introductionmentioning
confidence: 99%
“…Due to their powerful anti-inflammatory effects, it is plausible that DMARDs may also prevent cardiovascular events. Inhibition of cytokines, such as tumor necrosis factor (TNF) and interleukins (ILs), and janus kinase (JAK) have been reported to limit inflammatory mechanisms implicated in athero-thrombosis through studies in animal models 10 12 . Most commonly prescribed biologic and targeted synthetic DMARDs such as TNF-alpha (α) inhibitors, IL-1 beta (β) & IL-12/23 inhibitors and JAK-1/2 inhibitors have been tested in randomized controlled trials within a variety of different populations that are at risk of MACE, such as people with rheumatoid arthritis and psoriasis 13 17 .…”
Section: Introductionmentioning
confidence: 99%
“…The previous study has shown that TNF-ɑ is a key pro-inflammatory marker, which also upregulates the VCAM-1 and ICAM-1 expressions and stimulates the adherence of monocytes to the endothelial surface [57]. The TNF-ɑ is primarily secreted by macrophages and further triggers the release of more inflammatory cytokines such as IL-1β, IFN-γ, and IL-6 [58]. We observed significant increases in the expressions of pro-inflammatory marker of TNF-ɑ and adhesion molecules VCAM-1 and ICAM-1, with simultaneous decrease in the expression of anti-inflammatory marker of IL-10 in the OB group.…”
Section: Discussionmentioning
confidence: 99%
“…Wolach and collaborators [66] demonstrated that, in a deep-vein-stenosis murine model, NET formation and thrombosis are blunted by inhibition of Jak2 with ruxolitinib. In a very recent study in rabbits fed a high-fat diet, ruxolitinib reduced the atherosclerosis induced in aorta by balloon injury [86]. Furthermore, it has been shown that the selective Jak2 inhibition with fedratinib reduces the formation of atherosclerotic plaque in Apoe-/-mice [87].…”
Section: Jak2 Inhibitorsmentioning
confidence: 98%